State Policy Reform and Tracking - Wilson, Bruce L.; Research for Better Schools, Inc., Philadelphia, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
As part of a larger study of policy implementation, this paper discusses the changes in five Maryland high schools regarding the reform of graduation requirements. The study hypothesized that tracking systems have a powerful influence on educational experiences and that reform intended to change those experiences would be mediated by track. In 1985, the Maryland State Board of Education mandated new graduation requirements, which included: 1) the addition of a third credit in mathematics and 2) the addition of an advanced high school diploma called the Certificate of Merit. The study sought to describe the student stratification systems in place prior to the implementation of the new policy and then to document any changes in those systems. Data were obtained from an analysis of student transcript records (which compared those of the class of 1986 with those of the class of 1989) and from interviews with a total of 343 teachers and 403 students. Findings indicate that, overall, students took more mathematics credits. Students in higher tracks persistently took more courses that would further their education and careers. However, the failure rates for lower track students increased. Also, there was some evidence that teachers did not uphold standards of high expectations for all. The unevenness in teacher knowledge about the Certificate of Merit helped to perpetuate inequities in access to educational opportunities. Three tables are included. Appendices contain frequency distributions of student transcripts by track and of student and teacher interviews by school and year. (LMI)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Academic Standards; Access to Education; Elementary Secondary Education; Grouping (Instructional Purposes); Social Stratification; State Curriculum Guides; State Standards; Student Placement; Track System (Education); Maryland; Speeches/Meeting Papers; Reports, Research